Developing Administrative Skills to Create a Relationship Dimension - Phrakhru Prapatpanyatorn,; Phrakhru Kowitbunkhet,; Phrabaidika Thawatchai Charanathammo,; Thapin, Amnaj (Dhammathas Academic Journal, 2023)
Good management must practice and develop management skills all the time. which has the process of studying and increasing the body of knowledge in management science and methods of management as an important basis, Self-improvement in Buddhism according to the Pali language is called attattha, self-benefit, and management skills development in the form of Developing management skills to create a relationship dimension is the development for the organization as a whole in Buddhism, called Prattha, benefits for others. But if the knowledge in management science and methods of management are also developed Develop management skills to create a relationship dimension, that is, develop yourself and develop for the organization as well. In Buddhism, it is called upayattha. The two benefits consist of 1) development of political cognitive skills, 2) development of conceptual skills that can analyze complexity, and 3) development of communication skills. The stimulating media is a model and authorization. 4) The development of analytical skills, the diagnostic process, management skills (Diagnosis) 5) The development of the ability to use information communication technology 6) The development of a big picture skill the impact of risk management for social responsibility (CSR Risk Management), both image and overview using a strategy for the future (Scenario Strategy) in this article, a model for developing managerial skills is presented to create a relationship dimension to study the relational dimensions of management skills and as a guideline for developing and integrating management styles in the 21st century, and for the benefit of the executives themselves in developing their management skills Beneficial to the organization by being able to manage the organization under changes to allow the organization to adapt and develop a management style, and benefit society resulting in development according to the goals and operational objectives of that organization.